RETRACTED: Use of Ore-Derived Humic Acids With Diverse Chemistries to Elucidate Structure-Activity Relationships (SAR) of Humic Acids in Plant Phenotypic Expression - Lamar, Richard T.; Monda, Hiarhi; Sleighter, Rachel (Frontiers in Plant Science, 2021)
We report the results of a structure-activity relationship study that was undertaken to identify humic substance chemistries that drive the plant biostimulant response. The effects of seven extensively chemically characterized, ore-derived humic acids (HA) on corn seedling biomass and root and shoot morphological parameters were investigated. Chemometric analyses were then conducted to identify correlations between HA chemical features and plant biomass and morphological charactersitics. The primary chemical driver of plant biomass and morphology was the ratio between HA electron accepting capacity (EAC) and electron donating capacity (EDC). The HA electron accepting capacity is found in quinones and semiquinone free radicals, while the HA electron donating capacity is found in polyphenolics and glycosylated polyphenolics. Based on our results, we propose a mechanism of action for ore-derived HA plant biostimulation that involves the interplay of pro-oxidants, in the form of quinones and semiquinone radicals, and antioxidants, in the form of polyphenols and possibly glycones and carbohydrates. The quinones/semiquinones initiate an oxidative stress response via the stimulation of transmembrane electron flow that results in both reactive oxygen species (ROS) production (i.e., an oxidative burst) and membrane depolarization, the latter of which allows Ca2+ flux from the apoplast into the cytoplasm. Based on the magnitude of depolarization, a specific cytoplasmic Ca2+ signature is produced. As a secondary messenger Ca2+, via binding to Ca2+- sensor proteins, transmits the signature signal, resulting in specific intracellular responses that include changes to plant morphology. The greater the EAC, the greater the ROS production and magnitude of plasma membrane depolarization and resulting stress response. The HA antioxidants are able to scavenge and quench the ROS and thus modulate the intensity and extent of the stress response to greater or lesser degrees, based on their concentrations and radical scavenging efficiencies, and thus modify the Ca2+ signature and ultimately the intracellular molecular responses.